Retrospective analysis of hairy vetch (Vicia villosa roth) poisoning in Argentina (2004–2019) - Aguirre Castro, Laura Sabrina (2021)
Hairy vetch (Vicia villosa) poisoning in cattle is characterized by a systemic granulomatous inflammatory response that resembles a type-IV hypersensitivity reaction. Hairy vetch toxicity has been described in cattle worldwide. The aim of this paper was to describe 10 outbreaks of hairy vetch poisoning in cattle studied at INTA EEA Salta and INTA EEA Balcarce, Argentina, from 2004 to 2019. Clinical signs included weakness, pyrexia, dermatitis, alopecia, and progressive weight loss, which leads to death over a clinical course of approximately two weeks. A total of 12 necropsies were performed and tissue samples were collected for histopathology. The main gross changes were observed in skin, lymph nodes, liver, heart, spleen and kidneys. Other tissues, such as pancreas, thyroid, and adrenal glands, were also affected. Histological lesions consisted of multifocal to diffuse granulomatous inflammation in those organs. The toxicity of hairy vetch has been described in several countries of the world. In Argentina, the use of hairy vetch as a cover crop has become common in some regions during the past years. The data suggest that hairy vetch poisoning is an important disease in cattle. More studies are needed to contribute with further information.